2008
DOI: 10.1111/j.1744-7909.2008.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Size‐number Distributions of Seeds for Use in Soil Bank Studies

Abstract: Knowledge of soil seed banks is essential to understand the dynamics of plant populations and communities and would greatly benefit from the integration of existing knowledge on ecological correlations of seed size and shape. The present study aims to establish a feasible and meaningful method to describe size-number distributions of seeds in multi-species situations. For that purpose, size-number distributions of seeds with known length, width and thickness were determined by sequential sieving. The most appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Data 2019, 4, 61 2 of 10 Therefore, we investigated [10] size-number distributions of seeds with known length, width, and thickness after being passed through a series of sieves. We found that the geometric mean of length, width, and thickness was the most adequate one-dimensional seed size estimator, providing shape-independent measures of seed volume which were directly mirrored by the sieves mesh side.…”
Section: Discussionmentioning
confidence: 99%
“…Data 2019, 4, 61 2 of 10 Therefore, we investigated [10] size-number distributions of seeds with known length, width, and thickness after being passed through a series of sieves. We found that the geometric mean of length, width, and thickness was the most adequate one-dimensional seed size estimator, providing shape-independent measures of seed volume which were directly mirrored by the sieves mesh side.…”
Section: Discussionmentioning
confidence: 99%
“…Either before or after tillage, non-spherical seeds were more abundant than spherical seeds, their percentage ranging between 53% (in nine cores taken before tillage) and 62% (in three cores taken after harrowing). Given the adequacy of mesh side to estimate seed volume [ 30 , 39 ] seed size was calculated and found to extend almost always across three orders of magnitude, and only in one sample across four orders of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…The approach and procedures of Casco et al . [ 30 ] were generally followed including the choice of mesh side instead of mesh bisector as a surrogate for seed size. All statistics were done with Statgraphics 4.2 (STSC, Inc., Rockville, MD, USA) except Box-Cox transformations done with BIOM (Applied Biostatistics, Inc., New York, NY, USA) and lack of fit tests done with Excel ® 2010 (Microsoft Corporation).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation